Analisis faktor yang mempengaruhi pendapatan usaha mikro binaan pusat layanan usaha terpadu (PLUT) di Paal Merah Kota Jambi - Nurul Hidayah; Umiyati, Etik; Parmadi, Parmadi (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2023)
This study objectives to analyze the influence of factors such as operating capital, length of business, working hours, and guidance on the development of micro-enterprises under the Center of Integrated Services of SMEsCo (PLUT) in Paal Merah, Jambi City. This research also shows the characteristics of each micro business that has been fostered. The method used in this study is a quantitative study with primary data and information obtained through observation, interviews and questionnaire surveys. As for this research, it shows that the variables of operating capital and length of business have a positive and significant influence on micro business income. Meanwhile, the variables of working hours and the level of coaching satisfaction only influence simultaneously but do not have a partial effect on the income of micro-businesses in the field of food assisted by PLUT in Paal Merah District, Jambi City